IEEE 2011 10th International Conference on Electronic Measurement &Amp; Instruments 2011
DOI: 10.1109/icemi.2011.6037849
|View full text |Cite
|
Sign up to set email alerts
|

Thickness precision measurement method of sheath and insulation materials based on image processing

Abstract: Subpixel is a key technology of image processing technology. It can achieve positioning better than entire pixel precision to the target. Against the shortcoming of slow speed of general Zernike moment subpixel location method, proposed an improved Sobel-Zernike moment positioning method in the software algorithms of sheath and insulation materials thickness image measurement system, improved the edge point criterion and the edge subpixel coordinates formula, optimized the edge of a single pixel contour, achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…According to one study [9], the rates of obtaining a diagnosis via transbronchial or percutaneous lung biopsy are statistically comparable at ~ 25%, while the corresponding rate for surgical lung biopsy is signi cantly higher (~ 98.7%). In the present study, diagnoses were obtained for 91.2% of the patients who underwent TBCB, that is, a lower rate obtained by surgical lung biopsy but higher than that of either transbronchial or percutaneous lung biopsy reported previously [7,9].…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…According to one study [9], the rates of obtaining a diagnosis via transbronchial or percutaneous lung biopsy are statistically comparable at ~ 25%, while the corresponding rate for surgical lung biopsy is signi cantly higher (~ 98.7%). In the present study, diagnoses were obtained for 91.2% of the patients who underwent TBCB, that is, a lower rate obtained by surgical lung biopsy but higher than that of either transbronchial or percutaneous lung biopsy reported previously [7,9].…”
Section: Discussioncontrasting
confidence: 53%
“…Thoracentesis or drainage was performed in those with moderate pneumothorax, while persistent pneumothorax did not occur. Cascante et al [7,16] reported similar results. Other studies have reported that complications such as postoperative infection, empyema, respiratory failure, short-term DLD exacerbation, and postoperative death are uncommon or rare [9,17,18], and these did not occur in our subjects.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations